Combination of Captopril with Gliclazide Decreases Vascular and Renal Complications and Improves Glycemic Control in Rats with Streptozotocin- Induced Diabetes Mellitus - Mizar, Sayed M.M.; Kozman, Magy R.; Abo-Saif, Ali A.; Messiha, Basim A.S. (Endocrine, Metabolic & Immune Disorders-Drug Targets, 2021)
Background: The common antihypertensive angiotensin-converting enzyme (ACE) inhibitor captopril was reported to possess anti-oxidant and anti-inflammatory effects in different experimental models. Diabetic vascular complications arise from increased vascular endothelial inflammation and oxidative stress as well as decreased nitric oxide bioavailability in the vessel walls due to poor glycemic control. Objective: This study aimed to evaluate the role of captopril and gliclazide in decreasing diabetes mellitus (DM) vascular complications caused by decreased cellular glucose uptake and impaired endothelial nitric oxide metabolism, as well as examine the effects of the combination on diabetic renal complication and plasma lipid profile. Methods: Adult male Wister rats received captopril (25 mg/kg/day) and/or gliclazide (10 mg/kg/- day) by oral gavage daily for one month after induction of DM using streptozotocin (50 mg/kg, i.p., once). Serum glucose and insulin levels, inflammatory mediators like TNF-α, oxidative stress biomarkers like glutathione and nitric oxide, and plasma lipid profile were measured. Besides, histopathological examination of the thoracic aorta and kidney tissues, Western blot assessed the expression of nitric oxide synthase (NOS) subtypes in the thoracic aorta. Results: Captopril significantly improved vascular architecture and oxidative stress and modulated nitric oxide synthesis via regulation of nitric oxide synthases, as well as decreased inflammation via down-regulating TNF-α, decreased systolic and diastolic blood pressure, and improved serum lipid profile in diabetic rats. Gliclazide increased serum insulin and decreased serum glucose, as well as its anti-oxidant and anti-inflammatory effects. Conclusion: Captopril showed a promising protective effect against DM vascular complications, at least via nitric oxide modulating effect, anti-oxidant effect, and anti-inflammatory activity that appeared in biochemical and histopathological findings, lipid profile, renal function, and architecture improvements. Combining gliclazide with captopril gives an additive effect through enhanced glycemic control and increased anti-oxidant and anti-inflammatory properties above captopril alone.
Keywords: hyperglycemia